Supporting Neighbourhood-based approaches to Addressing Poverty Concentration and its Impacts on Health - McMaster Health Forum (My University, 2011)
Video interviews with participants in a stakeholder dialogue about Supporting Neighbourhood-based approaches to Addressing Poverty Concentration and its Impacts on Health (on YouTube).
http://www.youtube.com/playlist?list=PL147290794A481D79&feature=plcp
Keywords: neighbourhood; poverty; health; Hamilton